Challenges of the curricularization of university extension in the context of educational transformation: Entrevista colectiva (Cuadernos de Extensión Universitaria de la UNLPam, 2024)
Within the framework of a transformation process in higher education supported by a series of public policies that promote the promotion of extension within the national university system, the curricularization of university extension has emerged as an issue of great relevance in various institutions. academics throughout the country. Its corollary was the execution of a specific budget item in 2021, the same year in which the document “Universities towards 2030” was developed by the National Interuniversity Council (CIN), which stated: “the training of university citizens, future professionals committed to the development of practices committed to improving the quality of life of our population, based on productive and social development, highlights the necessary incorporation of extension in the curriculum (...) re-signify the university curriculum from this perspective It necessarily implies giving relevance to the extension, but from a perspective of comprehensiveness, we understand that this is a debate that is always necessary and with which our system still owes a debt.”This text seeks to present the visions and experiences of the members of the university faculty who participated in the X National Congress of University Extension held at the National University of La Pampa in 2023, where the workshop “Students and curricularization of the extension” in which the student body who participated on behalf of the different universities in the country was promoted as the protagonist to exchange ways of observing, analyzing and putting extension into practice in the institutions.